Beyond the CCCM – The Conditions Facilitating the Swedish Climate Change Reactionary Movement - Vowles, Kjell; Ekberg, Kristoffer ; 0000-0002-1468-7283 (Environmental Communication, 2025)
Research on climate change obstruction has often focused on what has been called the Climate Change Countermovement, the CCCM. While the term originated from the social movements literature – acknowledging the movement-countermovement dynamics – it has in climate obstructionist research often been described as a relatively fixed entity connected to the vested interests of the fossil fuel industry and conservative think tanks. While this research has provided great insights regarding funding and strategies of professional actors, it is important to see how climate obstruction is not only about vested interests. By using the Swedish climate change reactionary movement as an example, we show how the work on countermovements by Suzanne Staggenborg and David S. Meyer, can highlight the importance of political allies, issue framing, and shifting media ecosystems for countermovement activity. In Sweden, this has resulted in climate obstruction gaining traction when the far right has led a broader backlash against progressive politics.
Keywords: Climate obstruction; far right; social movements; alternative media; countermovement